Current Alternations in Inflection of Polish Masculine Inanimate Nouns in the Singular: A Pilot Study - Mausch, Hanna (Investigationes Linguisticae, 2003)
This paper discusses current use of genitive and accusative case forms of common nouns borrowed from English that are increasingly present in Polish and identified as masculine inanimate by virtue of their consonantal offsets in the nominative singular (bare forms).* In the first part, an overview of approved usage is presented. That is, a survey the assignment of nouns to various inflectional patterns based on works of three acclaimed Polish linguists is offered. In the second part, a pilot study involving a test given to Polish students is discussed. Finally, standard patterns are compared to the actual usage of the nouns tested. The objective is to identify regularities in the assignment of case endings. Results of this pilot study are to be treated as hints for further research on current alternations in case forms.